2019
DOI: 10.1111/cen.14101
|View full text |Cite
|
Sign up to set email alerts
|

Circulating gut microbiota metabolite trimethylamine N‐oxide and oral contraceptive use in polycystic ovary syndrome

Abstract: Objectives: Polycystic ovary syndrome (PCOS) is associated with an increased cardiometabolic risk that might not necessarily translate into adverse cardiovascular outcome later in life. Recently, alterations in gut microbial composition have been reported in the syndrome. Microbiota-dependent metabolite trimethylamine N-oxide (TMAO) and its precursors are closely linked with development of atherosclerotic cardiovascular disease, independently of traditional risk factors. We aimed to assess whether TMAO and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 35 publications
(67 reference statements)
1
15
0
1
Order By: Relevance
“…Data from associative and mechanistic studies draw a strong link between dysbiosis and pathobiotic bacteria in the gut, the microbiota-dependent production of TMAO, and an increased risk of cardiometabolic and gastrointestinal disorders [ 98 , 113 , 150 , 151 , 152 , 153 ]. Since many of those disorders lack effective treatments, the gut microbiota has emerged as an attractive therapeutic target (see Table 3 ).…”
Section: Potential Therapies In Choline-related Diseasesmentioning
confidence: 99%
“…Data from associative and mechanistic studies draw a strong link between dysbiosis and pathobiotic bacteria in the gut, the microbiota-dependent production of TMAO, and an increased risk of cardiometabolic and gastrointestinal disorders [ 98 , 113 , 150 , 151 , 152 , 153 ]. Since many of those disorders lack effective treatments, the gut microbiota has emerged as an attractive therapeutic target (see Table 3 ).…”
Section: Potential Therapies In Choline-related Diseasesmentioning
confidence: 99%
“…Moreover, TMAO is considered a potential metabolite in the pathogenesis of PCOS. In a prospective study of 27 obese patients with PCOS, Eyupoglu et al found for the first time that TMAO and its precursors are elevated in women with PCOS compared with in healthy women, which seems to indicate that TMAO is associated with hyperandrogenism in PCOS [118]. Interestingly, another study suggested that elevated plasma TMAO levels may be associated with the pathogenesis of PCOS rather than hyperandrogenism [119].…”
Section: Trimethylamine N-oxidementioning
confidence: 99%
“…Among these factors, lifestyle factors (e.g., diet and exercise) act as pivotal determinants of the gut microbiome (50). Microbial-dependent metabolites have been found to be decreased in patients with PCOS after 3 months of oral contraceptive therapy along with a general dietary advice (51). This indicates that the gut microbiome of patients with PCOS can be affected by different lifestyles.…”
Section: Other Factorsmentioning
confidence: 99%